Enhancement Literacy through Read Aloud Relay - Nabilla Namira Permata Putri; Ali Mustadi (International Journal of Elementary Education, 2024)
Reading is very important to support academic achievement, but based on the observation results, the reading interest of grade 1 students is still low. A new, special strategy is needed that can help students improve their literacy and early reading skills. Therefore this study aims to analyze the strategy of implementing read aloud relay in building students' reading interest. This study is a qualitative study with data collection techniques in the form of interviews, observations and documentation conducted on 27 grade 1A students at elementary school. The data obtained were then analyzed according to Miles and Hubberman. The results of the study showed that read aloud relay applied during literacy hours and certain lesson hours can increase students' reading interest. In addition to developing reading interest through this strategy, it can also develop students' speaking and listening skills so that students understand what they are reading better. Therefore, read aloud relay can improve the literacy of grade 1 elementary school students.